Comparative study on the mechanisms of anti-lung cancer activities of three sulfated galactofucans. Issue 21 (30th September 2021) - Zhang, Wenjing; Wu, Wanli; Bao, Yizhong; Yan, Xiaojun; Zhang, Fuming; Linhardt, Robert J.; Jin, Weihua; Mao, Genxiang
Abstract : Sulfated galactofucans, as the active compositions of fucoidan, were reported to exhibit antitumor activity. Abstract : Sulfated galactofucans, as the active compositions of fucoidan, were reported to exhibit antitumor activity. In the current study, a sulfated galactofucan (SGF) from Sargassum thunbergii and its three derivatives (SGF-H, SGF-L, and SGF-S) were prepared for structural analysis. Structural analysis showed that SGF-H was a high molecular weight sulfated galactofucan (51.5/17.8 kDa) with a high molar ratio of galactose (Gal) to fucose (Fuc) (0.66 : 1), SGF-L was a low molecular weight sulfated galactofucan (17.7 kDa) with a low molar ratio of Gal to Fuc (0.20 : 1), and SGF-S was a mixture (1.7 kDa) of sulfated galacto-fuco-oligomers or fuco-oligomers. It was noteworthy that the linkage of Gal residues in SGF-H was a β-linkage while SGF-L was an α-linkage. A comparative study on the anti-lung cancer activity in vitro and in vivo, antimetastatic effects, the metastasis-associated protein expression, and binding abilities to fibroblast growth factors (FGFs) of SGF, SGF-H, and SGF-L was performed to understand the structure–activity relationship. To some extent, SGF-L showed the strongest activity in the inhibition of human lung cancer cells A549 cell proliferation, while SGF-H exhibited the strongest activity in the inhibition of human bronchial epithelial cells BEAS-2B cell proliferation. SGF-L showed the strongest antimetastatic activity, followed by SGF-H and SGF. The expression of metastasis-associated proteins showed only a small difference. The in vivo tumor inhibition of SGF, SGF-H, and SGF-L was 45%, 41%, and 31%, respectively. SPR analysis showed SGF-H binds preferentially to FGF1 and FGF2, while SGF-L preferentially binds to FGF7 and FGF10, suggesting that the anti-lung cancer activity from sulfated galactofucan could involve the FGF-FAK/mTOR pathway.